How emerging giants are rewriting the rules of M&A - KUMAR, Nirmalya (Institutional Knowledge at Singapore Management University, 2009)
While Western companies struggle with mergers and acquisitions, emerging giants like Indian aluminum producer Hindalco are using M&A as their main globalization strategy. That's partly because developing economies grew at near double-digit rates in the past 15 years, enabling many enterprises to make acquisitions. It's also because, according to the author's research, those corporations create more value from takeovers. To compete, Western multinationals should change their mind-set and shift the locus of their M&A efforts to regional headquarters in developing countries.U.S. and European companies, inhibited by slow-growing home markets, acquire rivals primarily to become bigger and thus create economies of scale. By contrast, emerging giants buy companies - often Western ones - to gain competencies that will help them become global leaders. They acquire only to meet strategic goals; they don't completely assimilate acquisitions; and their CEOs focus on the long term.Using this approach, Hindalco boosted revenues in seven years from $500 million to $15 billion. it acquired companies to expand its aluminum business, manufacture more value-added products, and extend its global reach. Rather than immediately seek targets overseas, the company patiently executed small takeovers, first in India and later abroad, before making a big global play. With each move, Hindalco climbed what the author calls an M&A competency stairway, gaining the skills it needed to pursue other targets. When it was ready, Hindalco bought Novelis, a North American corporation more than twice its size.Because of the global downturn, Hindalco will not realize the benefits of that acquisition as quickly as it had expected. But the fact that the company developed and adhered to a long-term M&A strategy will help it ride out the storm.